SUCCESSIVE MODEL OF MASTER TRAINING IN ENGINEERING - Sergey N. Postnikov (Высшее образование в России)
The article addresses the ways of improving training of masters in engineering. The paper reviews the existing approaches to master training in conformity with features of master training in engineering. The author proposes a model of master training based on successive bachelor and master programs. The elaborated algorithm allows to construct bachelor's and master's competence portrait. This portrait defines the structure and the content of training programs.